Prophets at loggerheads. Accusations of adultery in Jeremiah 239-15 - W. Wessels (Acta Theologica)
The focus of this article is on one aspect of the raging conflict between the prophetic parties addressed in Jeremiah 23:9-15. In this section the aspect of disloyalty to Yahweh is raised as hampering factor for being a true prophet. The research investigates the relationship between doing evil (cf. words such as adultery and ungodly/profane conduct) and the effect on the land (cf curse on the land, the land mourns, pastures drying up – 23:10-11). The research also entertains the relation with the next set of verses (23:13-15) which explicitly mentions the worship of Baal, the vegetation god, as reason for the disloyalty. The false prophets, with their adulterous way of living, are part of a leadership that failed the people of Judah and Yahweh.